Microgrid network design and control - Lew, King Loong. (2011)
Global warming, fossil fuel depletion, soaring fuel price and technological advancements are the key factors leading to a growing in the interest and use of Distributed Energy Resources (DER). DER includes different technologies that allow generation in small scale (microsources) and encourage the use renewable energy resources such as solar, wind or fuel cell. Large scale integration of DER into the energy production landscape can only be made possible with the introduction of a new control and management concept – the microgrid. This project aims to study and design a complete Microgrid network which incorporates the use of renewable distributed generators – photovoltaic system, wind turbine generator and fuel cell. Power electronics interface converter circuits which are required for the operation of a Microgrid are also modeled. The design concept of the Microgrid network and its control scheme is verified through simulation studies based on practical scenarios and the results obtained are then discussed.